Сутність та зміст змагальності сторін як основної конституційної засади судочинства - Міліціанов, Р. В.; Militsianov, R. V. (Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2014. – № 3. – С. 27-34, 2014)
Проаналізовано сутність та зміст конституційної засади судочинства змагальності сторін як правової категорії. Надано характеристику внутрішнього наповнення засади змагальності сторін. Визначено структуру, елементи та ознаки, які характеризують конституційну засаду змагальності сторін як цілісне поняття. Запропоновано практичні рекомендації щодо внесення змін до чинного законодавства України з метою розширення змагальних процедур.

This article analyzes the content and meaning of the constitutional principles of competitive justice as a legal category, the characteristic of internal filling of these principles is performed, its structure, elements and features, which characterize the competitiveness as a holistic concept, are determined Thus, the author analyzed the scientific work of local scientists who variously interpreted the nature and content of the parties’ competitiveness. As a result of a critical assessment of scientific works on this subject it was concluded that the parties’ competitiveness nature (in terms of its constitutional expression) is in procedural activity of the trial and court participant(s), based on the constitutional principles of the judiciary functioning, and is aimed at the decision of conflict relations by the court based on evidentiary materials. The essence of competition is also the fact that this constitutional principles of justice comes to the denial of a phenomenon or behavior requires a certain confrontation, conflict, dispute referred to the Court, during which the parties express their views on all legal issues mandatory participant legal proceedings – court, which, in turn, makes decisions, noting the validity of the position of one side. In this case, may be opposed to the interests of the parties, and the non-recognition or denial of certain rights or facts (including the guilt of a crime), circumstances, relationships, as well as in a separate proceeding before the court the applicant proves the legitimacy of their claims for which there is no dispute about the right material but not recognized the factual circumstances that affect the legal status of a person. Interested persons may express their objections to the application or to refrain from this, that make use of discretionary powers, which is a condition for the existence of competition. During the research the concept of "judicial competitiveness” was highlighted, as well it was provided the determination of the content of parties’ competitiveness principles as a set of legal doctrines, regulations, rules, procedural law, formed regulatory or during the law enforcement which exist at all stages of proceedings and determine the subjects of the process, their rights and responsibilities, provide these participants with the opportunity to achieve the goals through the implementation of competitive power and authority.

Проанализированы сущность и содержание конституционной основы судопроизводства состязательности сторон как правовой категории. Дана характеристика внутреннего наполнения основы состязательности сторон. Определены структура, элементы и признаки, характеризующие конституционную основу состязательности сторон как целостное понятие. Предложены практические рекомендации по внесению изменений в действующее законодательство Украины с целью расширения соревновательных процедур.
The content and meaning of parties’ competitiveness as a basic constitutional principles of justice
Сущность и содержание состязательности сторон как основной конституционной основы судопроизводства
Міліціанов, Р. В. Сутність та зміст змагальності сторін як основної конституційної засади судочинства / Міліціанов Р. В. // Вісник Запорізького національного університету. Сер.: Юрид. науки. – 2014. – № 3. – С. 27-34.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; конституційна засада змагальності сторін; constitutional basis of competition between the parties; конституционная основа состязательности сторон; судочинство; proceedings; судопроизводство; форми змагальності; forms of competition; формы состязательности; змагальність сторін; rivalry of the parties; состязательность сторон